No association between thrombosis and factor V gene polymorphisms in Chinese Han population - Yanqing, Hu; Fangping, Chen; Qinzhi, Xie; Zaifu, Jian; Guangping, Wang; Xiaoxia, Zuo; Xiaoqun, Pu; Xiaobo (Thrombosis and Haemostasis, 2003)
Activated protein C resistance (APCR) is the most common hereditary condition of thrombosis in Western countries. And it is significantly linked to a single nucleotide polymorphisms (SNPs) in the coagulation factor V gene that results in the mutations at R506, R306 and HR2 alleles. To determine the prevalence of APCR and its association with the factor V gene SNPs in Chinese Han thrombotic patients, we investigated a total of 346 Chinese thrombotic patients and 140 normal controls for APCR using the APTT-based assays, according to manufacturer’s instructions, APC ratio ≦2 indicated APC resistance. Mutations of factor V at R506, R306, HR2 allele were detected by PCRMnl/I, Bst/NI, Rsa/I digestion as described before respectively. The results showed that the incidence of APC resistance were 12.0% (12 of 100 cases) in acute cerebral thrombosis (ACT) patients (P <0.05), 13.5% (13 of 96 cases) in acute myocardial infarction (AMI) patients (P <0.05), 16.7% (10 of 60 cases) in deep venous thrombosis (DVT) patients (P <0.05), 15.6% (14 of 90 cases) in systemic lupus erythematosus (SLE) patients (P <0.05) and 5.0% (7 of 140 cases) in normal controls. APCR is associated with thrombotic events. But no factor V R506Q mutation (FV Leiden) was found in all 5 groups. Only one AMI patient and one DVT patient revealed heterozygous R306G mutation, which was confirmed by direct sequencing PCR products. Additionally, two SLE patients showed to be heterozygous HR2 allele for the first time in the Chinese Han population. We concluded that APC resistance in the Chinese Han population might not be associated with mutations of factor V at R506, R306 and HR2 polymorphisms. Some other factors might contribute to APC resistance in the Chinese Han population.
Keywords: Activated protein C resistance (APCR); factor V; single nucleotide polymorphisms (SNPs); thrombosis; Chinese Han population